Novel GNAI3 mutation in a Chinese family with auriculocondylar syndrome and treatment of severe dentofacial deformities: a 5-year follow-up case report - Yulin Shi; Liang Rong; Siying Liu; Yiwen Liu; Chunlin Zong; Jinbiao Lu; Hongtao Shang; Yang Xue; Lei Tian (BMC, 2024)
Abstract Background Auriculocondylar syndrome (ARCND) is an extremely rare autosomal dominant or recessive condition that typically manifests as question mark ears (QMEs), mandibular condyle hypoplasia, and micrognathia. Severe dental and maxillofacial malformations present considerable challenges in patients' lives and clinical treatment. Currently, only a few ARCND cases have been reported worldwide, but most of them are related to genetic mutations, clinical symptoms, and ear correction; there are few reports concerning the treatment of dentofacial deformities. Case presentation Here, we report a rare case of ARCND in a Chinese family. A novel insertional mutation in the guanine nucleotide-binding protein alpha-inhibiting activity polypeptide 3 (GNAI3) was identified in the patient and their brother using whole-exome sequencing. After a multidisciplinary consultation and examination, sequential orthodontic treatment and craniofacial surgery, including distraction osteogenesis and orthognathic surgery, were performed using three-dimensional (3D) digital technology to treat the patient's dentofacial deformity. A good prognosis was achieved at the 5-year follow-up, and the patient returned to normal life. Conclusions ARCND is a monogenic and rare condition that can be diagnosed based on its clinical triad of core features. Molecular diagnosis plays a crucial role in the diagnosis of patients with inconspicuous clinical features. We present a novel insertion variation in GNAI3, which was identified in exon 2 of chromosome 110116384 in a Chinese family. Sequential therapy with preoperative orthodontic treatment combined with distraction osteogenesis and orthognathic surgery guided by 3D digital technology may be a practical and effective method for treating ARCND.